Historic Abu Ghraib verdict: U.S. Contractor held accountable for torture - Andrea Mølgaard (Torture)
After years of legal battles, three Iraqi survivors of torture in the Abu Ghraib prison have secured justice in a historic victory in U.S. courts. The jury ruled in favour of the Iraqi plaintiffs, holding a private contractor, CACI, accountable for its role in the abuse and torture of detainees during the Iraq War.